The Role of the Family in the Epic Works of Leo Tolstoy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes family relations in the works of Leo Tolstoy, using the example of the work "War and Peace". The study reveals the main features of family life, including the dynamics of the relationship between parents and children, the role of marital ties, as well as the influence of the family context on the formation of the personality of the characters.